Evaluating Entrepreneurial Intention Among Pesantren Students: Fostering Empowerment Through Education - Abdurrohim Abdurrohim; Kusaeri Kusaeri (SYAMIL: Journal of Islamic Education, 2024)
This article aims to evaluate predictors and triggering factors of Muslim entrepreneurial intentions and their relationship to Islamic education, particularly in Islamic boarding schools as indigenous educational institutions. The study employs systematic literature review on two databases, namely Institute Of Education Sciences (ERIC) and Scopus, with the assistance of Publish or Perish version 8, spanning from 2015 to 2024. A total of 27 articles were found, with international index quality, consisting of 8 articles in Q1, 11 in Q2, 6 in Q3, and 2 in Q4, mostly using quantitative approaches. Meanwhile, the research objects consist of countries with Muslim populations, ranging from Indonesia, Pakistan, Iran, Malaysia, Bangladesh to Nigeria. Six instruments were identified for evaluation purposes, divided into two aspects: first, internal aspects including 1) empathy, 2) self-efficacy and internal locus of control, and 3) spiritual and religiosity motivation, and second, external aspects namely 1) moral obligation, 2) prior experiences, and 3) perceived behavioral support. Additionally, 4) leadership was also identified. All these factors serve as recommendations for policymakers to formulate and develop Islamic boarding school curriculum.